StMAPK1 functions as a thermos-tolerant gene in regulating heat stress tolerance in potato (Solanum tuberosum) - Zhu, Xi; Duan, Huimin; Zhang, Guodong; Jin, Hui; Xu, Chao; Chen, Shu; Zhou, Chuanmeng; Chen, Zhuo; Tang, Jinghua; Zhang, Yu (Frontiers in Plant Science, 2023)
Background and aims Mitogen-activated protein kinases (MAPKs) have been reported to respond to various stimuli including heat stress. This research aimed to investigate whether StMAPK1 is implicated in the transduction of the heat stress signal to adapt heat stress as a thermos-tolerant gene. Materials and methods Potato plants were cultivated under mild (30°C) and acute (35°C) heat stress conditions to analyze mRNA expression of StMAPKs and physiological indicators. StMAPK1 was up-regulated and down-regulated by transfection. Subcellular localization of StMAPK1 protein was observed by fluorescence microscope. The transgenic potato plants were assayed for physiological indexes, photosynthesis, cellular membrane integrity, and heat stress response gene expression. Results Heat stress altered the expression prolife of StMAPKs. StMAPK1 overexpression changed the physiological characteristics and phenotypes of potato plants under heat stresses. StMAPK1 mediates photosynthesis and maintains membrane integrity of potato plants in response to heat stress. Stress response genes (StP5CS, StCAT, StSOD, and StPOD) in potato plants were altered by StMAPK1 dysregulation. mRNA expression of heat stress genes (StHSP90, StHSP70, StHSP20, and StHSFA3) was affected by StMAPK1. Conclusions StMAPK1 overexpression increases the heat-tolerant capacity of potato plants at the morphological, physiological, molecular, and genetic levels.